Pengaruh Persepsi Aksesibilitas dan Gangguan Jalan Terhadap Kepuasan Bermukim: Studi Kasus Tol Serang-Panimbang - Faqihuddin, Tubagus Zakie (Jurnal Komposit: Jurnal Ilmu-ilmu Teknik Sipil, 2026)
Investment in roads such as toll roads is considered a catalyst for regional connectivity. On the other hand, there are negative and positive externalities that are felt in the area where the infrastructure is being developed. This research was conducted to identify the influence of perceived accessibility and highway nuisance experienced by residential areas due to the presence of new road infrastructure, specifically the Serang-Panimbang Toll Road. This research studied the extent of the impact of the perceived trade-off between increased accessibility and nuisance highway activities on residential satisfaction and the desire to move. The Structural Equation Modeling - Partial Least Square (SEM-PLS) method was used to examine the framework of influences shaping residential satisfaction. The analysis was based on a survei collected from 603 respondents lived within a 1000m radius of the Serang-Panimbang Toll Road Section 1, covering 3 districts/cities: Serang City, Serang Regency, and Lebak Regency. The constructs include components of perceived highway nuisance, perceived accessibility, perceived and residential characteristics, and socioeconomic characteristics. The results show that perceived highway disturbances (such as perceived noise, air pollution, and interaction restrictions/barrief effect), residential characteristics, and socioeconomic characteristics do not have a significant effect on residential satisfaction. However, increasing perceived accessibility (such as perceived destination attributes, activity distribution, travel resistance, and transportation supply) and perceived occupancy are important factors in increasing residential satisfaction. The results also show that perceived residential satisfaction still increases the moving intention.